Cyberpreneurship a new opportunity - Mohd Shariff, Balqis; Amirrudin, Faizatul Akmam (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
The Internet has changed the way of life.The emergence of the Internet has necessitated a shift from traditional businesses to digital enterprises. Virtual businesses that operate strictly online have resulted from this shift and the primary drivers in this new front are online entrepreneurs generally described as cyberpreneurs. A cyberpreneur creates a company based on electronic commerce (Carrier & Raymond, 2004). The digital age generation would instead go online to get information and transact businesses rather than spending time which may be used to accomplish different things to wander from one store to another, comparing product information and transacting businesses. This has necessitated the cyberpreneurs to be more innovative and creative to attract customers to visit their business pages online and complete buying transactions.